Program Screening Fleksibilitas Hamstring Gratis untuk Masyarakat Umum: Upaya Deteksi Dini Masalah Kesehatan dan Pencegahan Cedera - Catherine Hermawan Salim; Astrid Komala Dewi; Yurita Mailintina (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
objective to provide free hamstring flexibility screening services to the general public and can increase public awareness of the importance of hamstring flexibility in maintaining health and preventing injuries. Method: Participants who come for the screening session will be given information about the importance of hamstring flexibility and hamstring flexibility measurements will be made using the Straight Leg Raise (SLR) test. The examination method is carried out before and after the hamstring flexibility screening is carried out. In addition, participants were also given education on ways to improve hamstring flexibility and prevent injuries. Through education and free screening services, this program helps people to understand their health conditions and take appropriate preventive measures and increase public awareness of the importance of maintaining healthy muscles and joints to improve the overall quality of life. Results: Evaluate the test results to determine the level of hamstring flexibility of each participant, record each participant's hamstring flexibility test results on the data form. The data obtained using the pre and post tests with the results each showed an increase in values of 9.25 degrees. Conclusion: The results of the analysis showed that the average hamstring flexibility experienced a very significant increase before and after the intervention hamstring flexibility screening. Therefore, this study makes an important contribution to understanding the importance of improving hamstring flexibility in maintaining health and preventing injury.